Daleki Susreti - Zlender, Vilim (Croatia, 2014)
Vanja’s first visit to Moldova took an unexpected turn and became a long struggle to help the sick and the old on the margins of the Moldovan society. This struggle resulted in a modern nursing home built in Străşeni. Today, several years after she returned to Croatia, Vanja is preparing for her big return and reunion with people to whom she has become so deeply attached. In these short encounters Vanja and her collocutors unveil their inner worlds, their drives, differences and the tender feelings they have for one another. This is a film about the universal nature of human connections regardless of age and culture; it’s a film about the benefits of empathy, respect and care.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films